2021
DOI: 10.3389/fpsyg.2021.680277
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement and Conceptualization of Coping Responses in Pediatric Chronic Pain Populations: A Scoping Review

Abstract: Background: Pediatric chronic pain is a prevalent condition that requires significant coping to encourage optimal functioning; however, relevant research is vast, heterogeneous, and difficult to interpret. To date, no attempt has been made to map and summarize the measurement and conceptualization of coping responses in the context of pediatric chronic pain.Objectives: A scoping review was conducted to map and summarize the participant characteristics, methodologies, theoretical frameworks, and measures used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…25 How a youth copes with pain appears important, though conclusions are difficult to draw. The low conceptual clarity among studies published on the topic identified in a recent a scoping review 26 highlights the importance of methodological clarity in further studies.…”
mentioning
confidence: 99%
“…25 How a youth copes with pain appears important, though conclusions are difficult to draw. The low conceptual clarity among studies published on the topic identified in a recent a scoping review 26 highlights the importance of methodological clarity in further studies.…”
mentioning
confidence: 99%